Jawabanmu

2014-05-09T22:23:11+07:00
L i m               2x                 = l i m            2x               
x⇒0    2sinx + sin 2x              x⇒0 2sinx + 2sinxcosx
                                          = l i m            2x              
                                             x⇒0  2sinx(1 + c0s x)
                                         = l i m           1            
                                           x⇒0      1 + cos x
                                         =            1            
                                                 1 + cos 0
                                         =       1                     
                                               1 + 1
                                         = 1/2